The role of intellectual humility in predicting investigative behavioral tendencies in COVID-19 vaccine news - Abu Bakar Fahmi; Abdul Majid Utama (Jurnal Ilmiah Psikologi Terapan, 2022)
During Coronavirus Disease 2019 (COVID-19) pandemic, the spread of fake news on social media occurred massively. To avoid any negative impacts, people are expected to exhibit investigative behavior towards the news they encounter, including conducting fact checks. Previous research has shown that intellectual humility can influence investigative behavior when exposed to fake news about COVID-19. This study aims to examine intellectual humility’s ability to predict investigative behavior when dealing with news about the COVID-19 vaccine. The study involved 227 students (157 female and 70 male, M = 21, SD = 1.19) as respondents who were selected by convenience sampling. The instruments used in revealing the two variables are the General Intellectual Humility Scale, headlines of news articles about the COVID-19 vaccine, and the scale of investigative behavior tendencies towards news about the COVID-19 vaccine. The results showed that intellectual humility could predict investigative behavior towards fake (B = 0.89; 95% CI [0,62, 1,15], p < 0,001) and fact news headlines (B = 0,87; 95% CI [0,60, 1,15], p < 0,001) about the COVID-19 vaccine. This finding implies that higher intellectual humility in individuals is predicted to increase investigative behavior towards news about the COVID-19 vaccine.